Sejarah Berlakunya Hukum Pidana Islam di Nusantara - Achmad Irwan Hamzani (Jurnal Hikmatuna, 2016)
Field Islamic law the most widely replaced by Western law as a result of colonization in the Islamic world is criminal law. Islamic criminal law applied in sultanates Archipelago formally by the judiciary until disallowed by the Dutch colonists. Name of the legal institutions vary. The books of the law which is like a book referenced Simbur Cahaya in Palembang, Serat Angger-angger Suryangalam and Serat Suryangalam in Demak. The struggle between Islamic law inall fields, customary law and western law in the realm of academia and the history of its existence took place since the colonial period. Not a few legal experts view as if not knowing the existence of Islamic law inIndonesia. There are also views it as a subsystem of customary law. Colonial experience led to a strong spirit of the superiority of western law. Manyformer colonies even accidentally transplanted the law through the admissions process and acculturation.